2005
DOI: 10.1039/b417366j
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of completely processed calcium carbonate dust particles

Abstract: This study presents, for the first time, field evidence of complete, irreversible processing of solid calcium carbonate (calcite)-containing particles and quantitative formation of liquid calcium nitrate particles apparently as a result of heterogeneous reaction of calcium carbonate-containing mineral dust particles with gaseous nitric acid. Formation of nitrates from individual calcite and sea salt particles was followed as a function of time in aerosol samples collected at Shoresh, Israel. Morphology and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
222
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(239 citation statements)
references
References 81 publications
16
222
0
Order By: Relevance
“…273 As shown in Figure 5, surface adsorbed water has two distinctive 407 IR absorption peaks in the region extending from 1500 to 4000 cm -1 , one near 3400 cm -1 Microscopy (SEM) and Energy Dispersive X-ray analysis (EDX). Two years later the atmospheric 433 significance of this finding was supported by a field study, 245 which showed that dust particles 434 collected in Israel have been substantially processed in the atmosphere and could exist in aqueous 435 state even at very low RH (9-11%). Transmission Electron Microscopy can also be used to monitor 436 the morphology change of mineral dust particles.…”
Section: Ftir Measurements Of Water Uptake 403mentioning
confidence: 55%
See 2 more Smart Citations
“…273 As shown in Figure 5, surface adsorbed water has two distinctive 407 IR absorption peaks in the region extending from 1500 to 4000 cm -1 , one near 3400 cm -1 Microscopy (SEM) and Energy Dispersive X-ray analysis (EDX). Two years later the atmospheric 433 significance of this finding was supported by a field study, 245 which showed that dust particles 434 collected in Israel have been substantially processed in the atmosphere and could exist in aqueous 435 state even at very low RH (9-11%). Transmission Electron Microscopy can also be used to monitor 436 the morphology change of mineral dust particles.…”
Section: Ftir Measurements Of Water Uptake 403mentioning
confidence: 55%
“…Kanazawa, Japan Some Ca-rich particles contain substantial amount of chloride, and they existed in an amorphous state and were nearly spherical even under high vacuum. Laskin et al 245 collected mineral dust particles at Shoresh, Israel, and analyzed the morphology 1845 and composition of individual dust particles using scanning electron microscopy with energy 1846 dispersive analysis of X-ray (SEM-EDX). For the first time, they 245 provided field evidence that 1847 due to heterogeneous reactions with HNO3, solid nonspherical calcium carbonate particles were 1848 converted to spherical liquid droplets which contain Ca(NO3)2.…”
Section: Quartz 1803mentioning
confidence: 99%
See 1 more Smart Citation
“…[19] More recently, Laskin et al [2005b] found significant number of large droplets in-situ on the mountain site (Shoresh) in Israel. They also concluded that such droplets form when Ca-carbonate particles react with HNO 3 in the atmosphere.…”
Section: Spherical Mineral Dustmentioning
confidence: 99%
“…914 915 The carbonate component of mineral dust (calcite, CaCO 3 , and dolomite, CaMg(CO 3 ) 2 ) has been shown to be particularly reactive with trace atmospheric gases such as HNO 3 and N 2 O 5 (Krueger et al 2003;Mogili et al 2006). Single particle analysis measurements have shown that carbonates can be completely converted to nitrates in the atmosphere (Laskin et al 2005;Matsuki et al 2005). Consequently, it is expected that in the atmosphere freshly emitted, partially processed, and fully reacted CaCO 3 will be present.…”
Section: Introductionmentioning
confidence: 99%